Contamination of Arctic Lakes with Persistent Toxic PAH Substances in the NW Part of Wedel Jarlsberg Land (Bellsund, Svalbard) - Lehmann‐Konera, Sara; Ruman, Marek; Franczak, Łukasz; Polkowska, Żaneta (Water, 2020)
The expansion of glacier‐free areas in polar regions favours the appearance of lakes in the non‐glaciated parts of glacier basins. This paper presents the differentiation of organic compound concentrations in fifty‐four Arctic lakes collected in four locations (Logne Valley, in the vicinity of the Scott, Renard and Antonia glaciers). We cover meteorological measurements, chemical analysis of sixteen dioxin‐like compounds (Polycyclic Aromatic Hydrocarbons (PAHs)), formaldehyde (HCHO), sum parameters of phenolic compounds (Σphenols) and dissolved organic carbon (DOC). The most contaminated with PAH compounds were lakes exposed to the influence of the Greenland Sea (Logne Valley lakes) and to the prevailing winds (Scott and Renard lakes). Interpretation of the PAH compounds results allowed for identification of pyrogenic sources as the main sources of PAH compounds in the year 2012. The highest levels of HCHO and Σphenols were observed for the Scott lakes, while the highest DOC levels were noted in Antonia lakes.